Complex partial synchronization patterns in networks of delay-coupled neurons. (22nd July 2019) - Nikitin, D.; Omelchenko, I.; Zakharova, A.; Avetyan, M.; Fradkov, A. L.; Schöll, E.
Abstract : We study the spatio-temporal dynamics of a multiplex network of delay-coupled FitzHugh–Nagumo oscillators with non-local and fractal connectivities. Apart from chimera states, a new regime of coexistence of slow and fast oscillations is found. An analytical explanation for the emergence of such coexisting partial synchronization patterns is given. Furthermore, we propose a control scheme for the number of fast and slow neurons in each layer. This article is part of the theme issue 'Nonlinear dynamics of delay systems'.